Christian faith and multiculturalism in Indonesia: an effort to develop harmony based on religion - Bertuah Agustina Manik; Kris Nugroho; Dwi Windyastuti Budi H (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Indonesia is known as a country that has a pluralistic society. Diversity and diversity in a plural society can lead to many problems such as discrimination, violence, injustice. One feature is the diversity of religions, there are six religions recognized in Indonesia. Religious pluralism can be a trigger for disharmony in society. Disharmony because religion is not single because it is often accompanied by various interests such as politics, culture, and others. The writing of this article explains that the Christian faith as one of the religions in Indonesia can work in the same direction with the concept of multiculturalism to produce harmony in a pluralistic and pluralistic society like Indonesia. This writing uses qualitative interpretative and descriptive methods of understanding the Christian faith and multiculturalism. The explanation in this paper shows the real phenomenon that religion is often considered the cause of disharmony and multiculturalism can be a solution in a pluralistic and pluralistic society. This writing will be interesting when religion, especially the Christian faith can work together / in the same direction with multiculturalism to produce harmony in society. The results of this study are very useful to explain that religion (Christian faith) is not a cause of disharmony if done correctly. Christian faith does not conflict with multiculturalism which together can build harmony in the life of a pluralistic and pluralist society.